The Kalash Genetic Isolate? The evidence for recent admixture - Hellenthal, G; Falush, D; Myers, S; Reich, D; Busby, G; Lipson, M; Capelli, C; Patterson, N (Elsevier, 2016)
The recent paper “The Kalash Genetic Isolate: Ancient Divergence, Drift, and Selection”, by Ayub et al1 (AJHG 2015, 96:1-9) suggests that the Kalash people of present-day Pakistan experienced “no detectable gene flow from their geographic neighbors in Pakistan or from other extant Eurasian populations” since their split from those populations over 8000 years ago. They note that this finding of apparent genetic isolation contradicts the results of Hellenthal et al2, who inferred DNA introgression dated to 910-220BCE in an overlapping sample of Kalash individuals. Hellenthal et al2 inferred the (unknown) source of this DNA to have genetic similarities to a wide range of modern-day groups from West Asia and Europe, including Germany-Austria and Turkey, for example.